2007
DOI: 10.4319/lo.2007.52.6.2641
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal structure and excitation of primary motions in a strongly stratified lake

Abstract: A modal analysis in the horizontal plane was extended to a layer-stratified basin with irregular bathymetry, and the theory was applied to Lake Biwa to investigate the horizontal structure and excitation of the basin-scale internal waves and gyres. The horizontal structure of the basin-scale internal waves consisted of cyclonic and anticyclonic elliptic cells, each of which appeared to follow the dispersion relationship of Kelvin and Poincaré waves in elliptic basins. The internal waves were preferentially exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 49 publications
2
73
0
1
Order By: Relevance
“…For a particular basin geometry, horizontal modes can be decomposed into multiple fundamental modes oscillating in harmony side by side (Gó mez-Giraldo et al 2006). In simple terms, those modes are excited that match the spatial and temporal distribution of the imposed wind stress (Csanady 1973;Gó mez-Giraldo et al 2006;Shimizu et al 2007).…”
Section: S~4mentioning
confidence: 99%
“…For a particular basin geometry, horizontal modes can be decomposed into multiple fundamental modes oscillating in harmony side by side (Gó mez-Giraldo et al 2006). In simple terms, those modes are excited that match the spatial and temporal distribution of the imposed wind stress (Csanady 1973;Gó mez-Giraldo et al 2006;Shimizu et al 2007).…”
Section: S~4mentioning
confidence: 99%
“…According to the research about Lake Kinneret (Israel), internal waves play a significant part in the transportation of materials in the bottom boundary layer [13]. Internal waves have also been studied in Lake Biwa by field observation [14], modal analysis [15], and numerical simulation [16,17]. Kitazawa et al [18] showed that internal waves would affect the transportation of hypoxic waters in the bottom boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…[6] While cyclonic circulations are abundant in lakes and marginal seas [Emery and Csanady, 1973;Laval et al, 2005;Beletsky and Schwab, 2008], anticyclonic motions rarely dominate basin-scale circulation [Strub and Powell, 1986] and appear primarily as regional gyres [Beletsky et al, 1999;Rueda et al, 2005;Shimizu et al, 2007]. Even more rare are observations of thermocline depressions linked to anticyclonic gyres [Endoh and Okumura, 1993].…”
Section: Introductionmentioning
confidence: 99%